Effects of silver nanoparticles (Ag-NPs) on physiological and biochemical properties of tomato plants under drought stress - Akhoundnejad, Yelderem; Karakaş, Özgür; Dasgan, Hayriye Yildiz; Sevgin, Nevzat; Gundogdu, Gamze; Temur, Baki (My University, 2023)
In this study, the effects of five different concentrations of silver nanoparticles (Ag-NPs) (0, 25, 50, 75, 100 mg$l^{-1}$) application on two different tomato cultivars grown at three different irrigation levels (25%, 50% and 100%) were investigated. Yield and quality characteristics of tomato fruits were investigated. The level of Ag-NPs that reduces the effects of arid stress on the plant genotypes physiologically and morphologically and their effects on the yield and fruit quality characteristics were also evaluated. Ag-NPs of 50 mg $l^{-1}$ application was found to be more effective than the other applications in protecting tomato plants against the negativities caused by drought stress. In general, the total yield showed a decrease in AgNPs+stress applications according to Chlorophyll (SPAD) and Water use efficiency. In total yield Ag-NPs, Ag-NPs+50% stress and Ag-NPs+25% stress applications, the highest doses were found for Ag-NPs 25 mgl-1 (5489.66 g m2) and Ag-NPs 25 mg $l^{-1}$ (4896.00 g $m^2$), respectively. This study provides results that may be used by producers in places where tomato plants grown in arid regions. Silver nanoparticles can be used at ppm levels to produce quality tomato fruits by providing drought resistance of the plant.
Keywords: Tomato; Drought; Stress; Silver nanoparticles